Parental Engagement in Education through the Lens of Social Capital - Pant, Khagendra Raj; Pant, Khem Raj (KMC Journal, 2025)
This qualitative case study explores the complex and lived experiences of parental and community involvement in school education within the rural setting of Kailali District, Nepal. It specifically examines the experiences of the Tharu indigenous ethnic group, Dalit communities, and economically disadvantaged families within a single, large and leading school in Bhajani Municipality. Data were collected through in-depth interviews and observations with 12 participants and analyzed thematically, drawing on Coleman’s social capital theory and the Epstein model. Findings reveal a complex and uneven landscape of involvement. While the community has historically supported local schools through financial and labor contributions, direct parental engagement in children’s learning is largely concentrated among socio-economically advantaged families. Educated parents demonstrate a greater capacity to influence school governance and directly support their children’s academic progress. Conversely, economic constraints, low literacy and migration patterns significantly limit the involvement of a substantial portion of the population. The study underscores the need to address these disparities to foster more equitable and inclusive school-community relationships and improve children’s educational outcomes in this rural Nepalese context.